A Review on Biohydrogen Production Through Dark Fermentation, Process Parameters and Simulation - Babak Mokhtarani; Jafar Zanganeh; Behdad Moghtaderi (Energies)
This study explores biohydrogen production through dark fermentation, an alternative supporting sustainable hydrogen generation. Dark fermentation uses organic waste under anaerobic conditions to produce hydrogen in the absence of light. Key process parameters affecting hydrogen yield, including substrate type, microorganism selection, and fermentation conditions, were examined. Various substrates, such as organic wastes and carbohydrates, were tested, and the role of anaerobic and facultative anaerobic microorganisms in optimizing the process was analyzed. The research also focused on factors such as pH, temperature, and hydraulic retention time to enhance yields and scalability. Additionally, the study modelled the process using ASPEN Plus software 14. This simulation identifies the bottle necks of this process. Due to the lack of available data, modelling and simulation of the described processes in ASPEN Plus required certain approximations. The simulation provides insight into the key challenges that need to be addressed for hydrogen production. Future research should indeed explore current limitations, such as substrate efficiency, process scalability, and cost-effectiveness, as well as potential advancements like the genetic engineering of microbial strains and improved bioreactor designs.